Dlouhé nekódující RNA v patofyziologii aterosklerózy - Novak, Jan; Vašků, Julie Bienertová; Souček, Miroslav (Vnitrni lekarstvi, 2018)
The human genome contains about 22 000 protein-coding genes that are transcribed to an even larger amount of messenger RNAs (mRNA). Interestingly, the results of the project ENCODE from 2012 show, that despite up to 90 % of our genome being actively transcribed, protein-coding mRNAs make up only 2-3 % of the total amount of the transcribed RNA. The rest of RNA transcripts is not translated to proteins and that is why they are referred to as "non-coding RNAs". Earlier the non-coding RNA was considered "the dark matter of genome", or "the junk", whose genes has accumulated in our DNA during the course of evolution. Today we already know that non-coding RNAs fulfil a variety of regulatory functions in our body - they intervene into epigenetic processes from chromatin remodelling to histone methylation, or into the transcription process itself, or even post-transcription processes. Long non-coding RNAs (lncRNA) are one of the classes of non-coding RNAs that have more than 200 nucleotides in length (non-coding RNAs with less than 200 nucleotides in length are called small non-coding RNAs). lncRNAs represent a widely varied and large group of molecules with diverse regulatory functions. We can identify them in all thinkable cell types or tissues, or even in an extracellular space, which includes blood, specifically plasma. Their levels change during the course of organogenesis, they are specific to different tissues and their changes also occur along with the development of different illnesses, including atherosclerosis. This review article aims to present lncRNAs problematics in general and then focuses on some of their specific representatives in relation to the process of atherosclerosis (i.e. we describe lncRNA involvement in the biology of endothelial cells, vascular smooth muscle cells or immune cells), and we further describe possible clinical potential of lncRNA, whether in diagnostics or therapy of atherosclerosis and its clinical manifestations.Key words: atherosclerosis - lincRNA - lncRNA - MALAT - MIAT.
Keywords: RNA dlouhá nekódující; ateroskleróza; Humans; Atherosclerosis; RNA, Long Noncoding; lidé